Composite negative pole piece for sodium ion battery, preparation method of composite negative pole piece and sodium ion battery

By designing a composite negative electrode sheet with functional layer and structural layer, using materials such as metal fluoride and hard carbon materials, the problems of low energy density and capacity attenuation of sodium ion batteries are solved, and the energy density and cycle life of the battery are significantly improved.

CN119560657AInactive Publication Date: 2025-03-04JIANGSU YIN GONG TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510125305.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-27
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The energy density of existing sodium ion batteries is low, which limits their use in high-end applications such as electric vehicles and mobile devices. The stability of metal sodium anode is poor, making it difficult to process into thin sodium anode.

Method used

A composite negative electrode sheet with functional layer and structural layer was designed, and functional materials such as metal fluoride and metal oxide were introduced into the functional layer. The structural layer uses a combination of hard carbon materials and binder to improve sodium ion deposition and peeling efficiency through the laminated structure and porous structure.

Benefits of technology

It significantly improves the energy density of sodium ion batteries, slows down capacity attenuation, and significantly improves cycle life, allowing sodium ion batteries to be used in a wider range of applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560657A_ABST
    Figure CN119560657A_ABST
Patent Text Reader

Abstract

The invention provides a composite negative pole piece for a sodium-ion battery, a preparation method of the composite negative pole piece and the sodium-ion battery, and belongs to the technical field of battery materials. The composite negative electrode plate comprises a negative electrode current collector and a negative electrode active layer arranged on at least one side surface of the negative electrode current collector; along the direction away from the negative electrode current collector, the surface of the negative electrode active layer comprises a functional layer and a structural layer which are laminated; the functional layer comprises a first negative electrode active material, a first binder and a functional material, and the functional material comprises metal fluoride and / or metal oxide; the structural layer includes a second negative electrode active material and a second binder. According to the composite negative pole piece, the sodium ion deposition and stripping efficiency is improved, the energy density of the sodium ion battery is improved, the capacity fading of the sodium ion battery is slowed down, and the cycle life of the sodium ion battery is prolonged. According to the composite negative pole piece, the sodium ion battery can be used in a wider application field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a composite negative electrode sheet for a sodium ion battery, a preparation method thereof, and a sodium ion battery. Background Art

[0002] Under the current social demand for sustainable energy utilization, sodium-ion batteries have great economic advantages due to their abundant raw materials and low prices.

[0003] Sodium-ion batteries achieve charge transfer through the insertion and extraction of sodium ions between the positive and negative electrodes. Due to the large atomic size and type of sodium, the energy density of current sodium-ion batteries (full batteries based on insertion reactions) is generally low. This problem limits their use in high-end applications such as electric vehicles and mobile devices.

[0004] At present, in order to improve the energy density of sodium-ion batteries, one of the solutions is to replace the embedded electrodes in sodium-ion batteries with metallic sodium anodes. However, even in relatively dry air, the stability of metallic sodium is still poor, and metallic sodium is difficult to be processed into thin sodium anodes. In most of the work reported so far, excessive metallic sodium anodes with uncontrollable thickness are used, which greatly affects the energy density and large-scale production. In addition, the low energy density of sodium-ion batteries mainly comes from the limitations of electrode materials and battery design. The electrochemical reaction characteristics used in current sodium-ion batteries also cause the problem of low energy density. Based on this, researchers have begun to look for more active and stable materials to improve the energy density of sodium-ion batteries. For example, materials such as sodium metal, sodium cobalt oxide, and sodium lithium iron phosphate are considered to have potential application prospects. At the same time, the electrolyte of sodium-ion batteries also needs to be improved to improve its ion conductivity and stability to support higher energy density. In addition to material selection and design, optimizing battery structure is also the key to improving energy density. It is crucial to design a more efficient battery structure to improve the ion and electron transport between the anode and cathode. In addition, optimizing the charging and discharging process of the battery to reduce losses and improve energy conversion efficiency is also the key to improving energy density.

[0005] In summary, how to further improve the energy density of sodium-ion batteries so that they can be used in a wider range of application fields is the focus of future development of sodium-ion battery technology. Summary of the invention

[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a composite negative electrode sheet for a sodium ion battery, a preparation method thereof, and a sodium ion battery. The present invention designs a composite negative electrode sheet having a functional layer and a structural layer, which not only improves the efficiency of sodium ion deposition and stripping, thereby improving the energy density of the sodium ion battery, but also slows down the capacity decay of the sodium ion battery, significantly improving the cycle life of the sodium ion battery. The composite negative electrode sheet enables sodium ion batteries to be used in a wider range of application fields, making an important contribution to a more sustainable energy future.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a composite negative electrode plate for a sodium ion battery, the composite negative electrode plate comprising a negative electrode current collector and a negative electrode active layer disposed on at least one side surface of the negative electrode current collector.

[0009] Along the direction away from the negative electrode current collector, the surface of the negative electrode active layer includes a stacked functional layer and a structural layer.

[0010] The functional layer includes a first negative electrode active material, a first binder and a functional material, and the functional material includes a metal fluoride and / or a metal oxide.

[0011] The structural layer includes a second negative electrode active material and a second binder.

[0012] The present invention designs a composite negative electrode pole piece with a functional layer and a structural layer. The composite negative electrode pole piece not only improves the efficiency of sodium ion deposition and stripping, thereby improving the energy density of the sodium ion battery, but also slows down the capacity decay of the sodium ion battery, significantly improving the cycle life of the sodium ion battery. The composite negative electrode pole piece enables the sodium ion battery to be used in a wider range of application fields, contributing to a more sustainable energy future.

[0013] The present invention introduces functional materials into the functional layer, which have a high deposition potential and can provide sodium nucleation sites, induce a uniform and dense deposition interface, reduce the generation of sodium dendrites, and help to improve the cycle life of the sodium ion battery.

[0014] Preferably, the functional material includes metal fluorides, metal oxides and alloys.

[0015] In the present invention, metal fluoride and metal oxide cooperate with each other to have higher energy density, better rate performance and cycle stability. At the same time, alloy materials are introduced to provide a framework, which is conducive to the deposition of sodium ions.

[0016] Preferably, the mass ratio of the metal fluoride to the metal oxide is (0.1-100):(0.1-50), wherein the selection range of the metal fluoride "0.1-100" can be, for example, 0.1, 1, 5, 10, 25, 50, 75 or 100, etc., and the selection range of the metal oxide "0.1-50" can be, for example, 0.1, 1, 5, 10, 20, 25, 30, 40 or 50, etc.

[0017] In the present invention, metal fluoride and metal oxide in a suitable mass ratio cooperate with each other, which is beneficial to the deposition of sodium ions and improves the rate performance and cycle stability.

[0018] Preferably, based on the mass of the functional layer, the mass proportion of the alloy is 0.1-20%, for example, it may be 0.1%, 0.5%, 1%, 5%, 10%, 15% or 20%.

[0019] Preferably, the metal fluoride includes any one of ZnF2, MgF2, CaF2, NaF or BaF2, or a combination of at least two thereof.

[0020] Preferably, the metal oxide includes any one of ZnO, MgO, CuO, CaO, Al2O3, La2O3 or Ce2O3, or a combination of at least two thereof.

[0021] Exemplarily, the alloy may be a Zn—Sn alloy, but is not limited thereto.

[0022] In the present invention, the role of introducing the alloy is to form a metal framework to reduce the sodium ion deposition energy, which is beneficial to inducing the sodium ion deposition and forming a better morphology.

[0023] Preferably, based on the mass of the functional layer, the mass proportion of the functional material is 0.1-20%, for example, it may be 0.1%, 0.5%, 1%, 5%, 10%, 15% or 20%.

[0024] In the present invention, the functional material with an appropriate mass content is beneficial to improving the cycle stability, rate performance and energy density of the battery cell.

[0025] Preferably, the thickness of the functional layer is 1-10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.

[0026] Preferably, the functional layer is a porous structure.

[0027] Preferably, the porosity of the functional layer is 20-70%, for example, 20%, 30%, 40%, 50%, 60% or 70%.

[0028] In the present invention, the functional layer with appropriate porosity helps to quickly deintercalate sodium ions and improve the kinetic performance and rate performance. In addition, the functional layer with porosity helps to reduce the mass of the negative electrode sheet.

[0029] Preferably, the average pore size of the functional layer is 0.1-200 nm, for example, 0.1 nm, 1 nm, 5 nm, 10 nm, 50 nm, 100 nm, 150 nm or 200 nm.

[0030] Preferably, the functional layer includes at least 2 functional single layers, for example, 2 layers, 3 layers, 4 layers, 5 layers or 10 layers.

[0031] Preferably, the thickness of the functional single layer is 0.1-5 μm, for example, 0.1 μm, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.

[0032] Preferably, along the direction away from the negative electrode current collector, the mass proportion of the functional material in the functional single layer increases layer by layer.

[0033] In the present invention, at least two functional monolayers increase in mass proportion of functional materials layer by layer along the direction away from the negative electrode current collector. This limitation is beneficial to improving interface stability and energy density, avoiding excessive accumulation of functional materials in the area close to the current collector, increasing the sodium ion transmission rate, and effectively avoiding the occurrence of unnecessary side reactions, and can also play a role in reducing costs.

[0034] Preferably, the first binder includes any one of PVDF (polyvinylidene fluoride), PAA (polyacrylic acid), PTFE (polytetrafluoroethylene), CMC (carboxymethyl cellulose) or SBR (styrene-butadiene rubber), or a combination of at least two of them.

[0035] Preferably, based on the mass of the functional layer, the mass proportion of the first binder is 0.1-4%, for example, it may be 0.1%, 0.5%, 1%, 2%, 3% or 4%.

[0036] Preferably, the first negative electrode active material includes any one of activated carbon, expanded graphite, carbon nanotubes or hard carbon, or a combination of at least two of them.

[0037] Preferably, the second negative electrode active material includes any one of activated carbon, expanded graphite, carbon nanotubes or hard carbon, or a combination of at least two thereof.

[0038] Preferably, based on the mass of the structural layer, the mass proportion of the second negative electrode active material is 80-98%, for example, 80%, 85%, 90%, 95% or 98%.

[0039] Preferably, the second binder includes any one of PVDF (polyvinylidene fluoride), PAA (polyacrylic acid), PTFE (polytetrafluoroethylene), CMC (carboxymethyl cellulose) or SBR (styrene-butadiene rubber), or a combination of at least two of them.

[0040] Preferably, the thickness of the structural layer is 10-60 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm or 60 μm.

[0041] Preferably, the porosity of the structural layer is 30-85%, for example, it may be 30%, 40%, 50%, 60%, 70%, 80% or 85%.

[0042] In the present invention, the structural layer with appropriate porosity helps to improve the kinetic performance of sodium ions and enhance the rate performance of the battery cell. In addition, the structural layer with porosity helps to reduce the mass of the negative electrode sheet.

[0043] Preferably, the average pore size of the structural layer is 0.1-200 nm, for example, 0.1 nm, 1 nm, 5 nm, 10 nm, 50 nm, 100 nm, 150 nm or 200 nm.

[0044] In a second aspect, the present invention provides a method for preparing a composite negative electrode sheet for a sodium ion battery as described in the first aspect, the preparation method comprising the following steps:

[0045] The first negative electrode active material, the first binder, the functional material and the solvent are mixed to obtain a functional layer slurry; the second negative electrode active material, the second binder and the solvent are mixed to obtain a structural layer slurry; wherein the functional material includes metal fluoride and / or metal oxide.

[0046] The functional layer slurry is coated on at least one side surface of the negative electrode current collector to form a functional layer, and then the structural layer slurry is coated on the outer surface of the functional layer to form a structural layer to obtain the composite negative electrode sheet for the sodium ion battery.

[0047] Preferably, the preparation method comprises the following steps:

[0048] (1) A first negative electrode active material, a first binder and a functional material are mixed, and then a solvent is added to prepare a functional layer slurry with a solid content of 30-50% (for example, 30%, 40% or 50%); wherein the functional material includes metal fluoride, metal oxide and alloy.

[0049] The second negative electrode active material and the second binder are mixed, and then a solvent is added to prepare a structural layer slurry with a solid content of 30-50% (eg, 30%, 40% or 50%).

[0050] (2) The functional layer slurry is coated (for example, by a coating method, but not limited thereto) on one surface of a negative electrode current collector (for example, an aluminum foil, etc.), and dried to obtain a functional layer.

[0051] The structural layer slurry is coated (for example, by a coating method, but not limited thereto) on the outer surface of the functional layer, and dried to obtain the structural layer.

[0052] (3) Repeat step (2) on the other side of the negative electrode current collector to obtain a composite negative electrode sheet for a sodium ion battery coated with a negative electrode active layer on both sides.

[0053] In a third aspect, the present invention provides a sodium ion battery, wherein the sodium ion battery comprises the composite negative electrode sheet for a sodium ion battery as described in the first aspect.

[0054] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0055] Compared with the prior art, the present invention has the following beneficial effects:

[0056] (1) The present invention designs a composite negative electrode sheet having a functional layer and a structural layer. By introducing a functional material into the functional layer, the functional material can provide a sodium nucleation site due to its high deposition potential, induce a uniform and dense deposition interface, reduce the generation of sodium dendrites, and help slow down the capacity decay of the sodium ion battery and improve the cycle life of the sodium ion battery.

[0057] (2) The composite negative electrode plate designed in the present invention improves the efficiency of sodium ion deposition and stripping, thereby significantly improving the energy density of the sodium ion battery. The energy storage capacity of the composite negative electrode plate is 1166 mAh / g of zero-valent sodium (that is, each gram of sodium can provide 1166 mAh of charge during the battery charging and discharging process).

[0058] (3) The composite negative electrode designed in the present invention enables sodium-ion batteries to be used in a wider range of applications, making an important contribution to a more sustainable energy future. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 This is a schematic diagram of the structure of the composite negative electrode sheet provided by the present invention.

[0060] Among them, 1-negative electrode current collector; 2-functional layer; 3-structural layer. DETAILED DESCRIPTION

[0061] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0062] Example 1

[0063] This embodiment provides a composite negative electrode sheet, and its structural schematic diagram is as follows: Figure 1 As shown, the composite negative electrode sheet includes a negative electrode current collector 1 and a negative electrode active layer arranged on both side surfaces of the negative electrode current collector.

[0064] The negative electrode active layer includes a stacked functional layer 2 and a structural layer 3 along a direction away from the negative electrode current collector 1; the functional layer 2 has a thickness of 2 μm, a porous structure, a porosity of 40%, and an average pore size of 50 nm; the structural layer 3 has a thickness of 10 μm, a porosity of 80%, and an average pore size of 100 nm.

[0065] The functional layer 2 includes a first negative electrode active material, a first binder and a functional material, the first negative electrode active material is a hard carbon material, the first binder includes CMC and SBR in a mass ratio of 1:1.5, the functional material is a metal fluoride, and the metal fluoride is MgF2.

[0066] The structural layer 3 includes a second negative electrode active material and a second binder, wherein the second negative electrode active material is a hard carbon material, and the second binder includes CMC and SBR in a mass ratio of 1:1.5.

[0067] Based on the mass of the functional layer 2 , the mass of the functional material accounts for 1%, and the mass of the first binder accounts for 0.25%; based on the mass of the structural layer 3 , the mass of the second negative electrode active material accounts for 97.5%.

[0068] This embodiment also provides a method for preparing the composite negative electrode sheet, the method comprising the following steps:

[0069] (1) The hard carbon material, CMC, SBR and MgF2 were mixed in a mass ratio of 98.75:0.1:0.15:1, and then deionized water was added as a solvent and stirred to prepare a functional layer slurry with a solid content of 40%.

[0070] The hard carbon material, CMC and SBR were mixed in a mass ratio of 97.5:1:1.5, and then deionized water was added as a solvent and stirred to prepare a structural layer slurry with a solid content of 40%.

[0071] (2) An aluminum foil with a thickness of 13 μm was selected as the negative electrode current collector, and the functional layer slurry was coated on one surface of the aluminum foil by a transfer coating method. After coating, the aluminum foil was dried at 80° C. to obtain a functional layer.

[0072] The structural layer slurry was coated on the outer surface of the functional layer by transfer coating, and dried at 80° C. to obtain a structural layer with a thickness of 10 μm.

[0073] (3) Repeat step (2) on the other surface of the aluminum foil to obtain a composite negative electrode sheet coated with a negative electrode active layer on both sides.

[0074] Example 2

[0075] This embodiment provides a composite negative electrode plate, which includes a negative electrode current collector and a negative electrode active layer arranged on both side surfaces of the negative electrode current collector.

[0076] The negative electrode active layer includes a stacked functional layer and a structural layer along a direction away from the negative electrode current collector; the functional layer has a thickness of 2 μm, a porous structure, a porosity of 40%, and an average pore size of 50 nm; the structural layer has a thickness of 10 μm, a porosity of 80%, and an average pore size of 100 nm.

[0077] The functional layer includes a first negative electrode active material, a first binder and a functional material, the first negative electrode active material is a hard carbon material, the first binder includes CMC and SBR in a mass ratio of 1:1.5, and the functional material includes MgF2 and CaO in a mass ratio of 1:1.

[0078] The structural layer includes a second negative electrode active material and a second binder, wherein the second negative electrode active material is a hard carbon material, and the second binder includes CMC and SBR in a mass ratio of 1:1.5.

[0079] Based on the mass of the functional layer, the mass of the functional material accounts for 2%, and the mass of the first binder accounts for 0.25%; based on the mass of the structural layer, the mass of the second negative electrode active material accounts for 97.5%.

[0080] This embodiment also provides a method for preparing the composite negative electrode sheet, the method comprising the following steps:

[0081] (1) The hard carbon material, CMC, SBR, MgF2 and CaO were mixed in a mass ratio of 97.75:0.1:0.15:1:1, and then deionized water was added as a solvent and stirred to prepare a functional layer slurry with a solid content of 40%.

[0082] The hard carbon material, CMC and SBR were mixed in a mass ratio of 97.5:1:1.5, and then deionized water was added as a solvent and stirred to prepare a structural layer slurry with a solid content of 40%.

[0083] (2) An aluminum foil with a thickness of 13 μm was selected as the negative electrode current collector. The functional layer slurry was coated on one surface of the aluminum foil by a transfer coating method. After coating, the aluminum foil was dried at 80° C. to obtain a functional layer.

[0084] The structural layer slurry was coated on the outer surface of the functional layer by transfer coating, and dried at 80° C. to obtain a structural layer with a thickness of 10 μm.

[0085] (3) Repeat step (2) on the other surface of the aluminum foil to obtain a composite negative electrode sheet coated with a negative electrode active layer on both sides.

[0086] Example 3

[0087] This embodiment provides a composite negative electrode plate, which includes a negative electrode current collector and a negative electrode active layer arranged on both side surfaces of the negative electrode current collector.

[0088] The negative electrode active layer includes a stacked functional layer and a structural layer along a direction away from the negative electrode current collector; the functional layer has a thickness of 2 μm, a porous structure, a porosity of 40%, and an average pore size of 50 nm; the structural layer has a thickness of 10 μm, a porosity of 80%, and an average pore size of 100 nm.

[0089] The functional layer includes a first negative electrode active material, a first binder and a functional material, the first negative electrode active material is a hard carbon material, the first binder is PVDF, and the functional material includes ZnF2 and MgO in a mass ratio of 1:1.

[0090] The structural layer includes a second negative electrode active material and a second binder, wherein the second negative electrode active material is a hard carbon material, and the second binder is PVDF.

[0091] Based on the mass of the functional layer, the mass of the functional material accounts for 2%, and the mass of the first binder accounts for 0.1%; based on the mass of the structural layer, the mass of the second negative electrode active material accounts for 97.5%.

[0092] This embodiment also provides a method for preparing the composite negative electrode sheet, the method comprising the following steps:

[0093] (1) The hard carbon material, PVDF, ZnF2 and MgO were mixed in a mass ratio of 97.9:0.1:1:1, and then N-methylpyrrolidone was added as a solvent and stirred to prepare a functional layer slurry with a solid content of 40%.

[0094] The hard carbon material and PVDF were mixed in a mass ratio of 97.5:2.5, and then N-methylpyrrolidone was added as a solvent and stirred to prepare a structural layer slurry with a solid content of 40%.

[0095] (2) An aluminum foil with a thickness of 13 μm was selected as the negative electrode current collector. The functional layer slurry was coated on one surface of the aluminum foil by a transfer coating method. After coating, the aluminum foil was dried at 80° C. to obtain a functional layer.

[0096] The structural layer slurry was coated on the outer surface of the functional layer by transfer coating, and dried at 80° C. to obtain a structural layer with a thickness of 10 μm.

[0097] (3) Repeat step (2) on the other surface of the aluminum foil to obtain a composite negative electrode sheet coated with a negative electrode active layer on both sides.

[0098] Example 4

[0099] This embodiment provides a composite negative electrode plate, which includes a negative electrode current collector and a negative electrode active layer arranged on both side surfaces of the negative electrode current collector.

[0100] The negative electrode active layer includes a stacked functional layer and a structural layer along a direction away from the negative electrode current collector; the functional layer has a thickness of 2 μm, a porous structure, a porosity of 40%, and an average pore size of 50 nm; the structural layer has a thickness of 10 μm, a porosity of 80%, and an average pore size of 100 nm.

[0101] The functional layer includes a first negative electrode active material, a first binder and a functional material, the first negative electrode active material is a hard carbon material, the first binder is PVDF, and the functional material includes ZnF2, MgF2 and MgO in a mass ratio of 1:1:1.

[0102] The structural layer includes a second negative electrode active material and a second binder, wherein the second negative electrode active material is a hard carbon material, and the second binder is PVDF.

[0103] Based on the mass of the functional layer, the mass of the functional material accounts for 3%, and the mass of the first binder accounts for 0.2%; based on the mass of the structural layer, the mass of the second negative electrode active material accounts for 97.5%.

[0104] This embodiment also provides a method for preparing the composite negative electrode sheet, the method comprising the following steps:

[0105] (1) The hard carbon material, PVDF, ZnF2, MgF2 and MgO were mixed in a mass ratio of 96.8:0.2:1:1:1, and then N-methylpyrrolidone was added as a solvent and stirred to prepare a functional layer slurry with a solid content of 40%.

[0106] The hard carbon material and PVDF were mixed in a mass ratio of 97.5:2.5, and then N-methylpyrrolidone was added as a solvent and stirred to prepare a structural layer slurry with a solid content of 40%.

[0107] (2) An aluminum foil with a thickness of 13 μm was selected as the negative electrode current collector. The functional layer slurry was coated on one surface of the aluminum foil by a transfer coating method. After coating, the aluminum foil was dried at 80° C. to obtain a functional layer.

[0108] The structural layer slurry was coated on the outer surface of the functional layer by transfer coating, and dried at 80° C. to obtain a structural layer with a thickness of 10 μm.

[0109] (3) Repeat step (2) on the other surface of the aluminum foil to obtain a composite negative electrode sheet coated with a negative electrode active layer on both sides.

[0110] Example 5

[0111] The difference between this embodiment and embodiment 1 is that the functional material is a combination of MgF2 and CaO with a mass ratio of 1:1.

[0112] The rest of the preparation methods and parameters were the same as those in Example 1.

[0113] Example 6

[0114] The difference between this embodiment and embodiment 1 is that the functional material is a combination of MgF2, CaO and Cu-Zn alloy, wherein the mass ratio of MgF2 to CaO is 1:1, and the mass of the alloy accounts for 10% of the total mass of the functional material.

[0115] The rest of the preparation methods and parameters were the same as those in Example 1.

[0116] Example 7

[0117] The difference between this embodiment and Embodiment 1 is that the functional material further includes a Cu-Zn alloy, and based on the mass of the functional material, the mass of the alloy accounts for 10%.

[0118] The rest of the preparation methods and parameters were the same as those in Example 1.

[0119] Example 8

[0120] The difference between this embodiment and Embodiment 1 is that the functional layer is composed of two functional single layers with a thickness of 1 μm, which are respectively denoted as the first functional single layer and the second functional single layer; along the direction away from the aluminum foil, the mass proportion of the functional material in the functional single layer increases layer by layer; each functional single layer is a porous structure with a porosity of 50% and an average pore size of 50 nm; each functional layer includes the hard carbon material, the first binder and the functional material.

[0121] Based on the mass in the first functional single layer, the mass proportion of the functional material is 1%; based on the mass in the second functional single layer, the mass proportion of the functional material is 5%.

[0122] The rest of the preparation methods and parameters were the same as those in Example 1.

[0123] Example 9

[0124] The difference between this embodiment and Embodiment 1 is that, based on the mass of the functional layer, the mass of the functional material accounts for 10%.

[0125] The rest of the preparation methods and parameters were the same as those in Example 1.

[0126] Example 10

[0127] The difference between this embodiment and embodiment 1 is that, based on the mass of the functional layer, the mass of the functional material accounts for 20%.

[0128] The rest of the preparation methods and parameters were the same as those in Example 1.

[0129] Embodiment 11

[0130] The difference between this embodiment and embodiment 1 is that the mass ratio of MgF2 to ZnO is 0.1:55.

[0131] The rest of the preparation methods and parameters were the same as those in Example 1.

[0132] Example 12

[0133] The difference between this embodiment and embodiment 1 is that the mass ratio of MgF2 and ZnO is 105:0.1.

[0134] The rest of the preparation methods and parameters were the same as those in Example 1.

[0135] Example 13

[0136] The difference between this embodiment and embodiment 1 is that, based on the mass of the functional layer, the mass proportion of the functional material is 0.05%.

[0137] The rest of the preparation methods and parameters were the same as those in Example 1.

[0138] Embodiment 14

[0139] The difference between this embodiment and embodiment 1 is that, based on the mass of the functional layer, the mass of the functional material accounts for 25%.

[0140] The rest of the preparation methods and parameters were the same as those in Example 1.

[0141] Embodiment 15

[0142] The difference between this embodiment and embodiment 1 is that the porosity of the functional layer is set to 15% by adjusting the drying temperature.

[0143] The rest of the preparation methods and parameters were the same as those in Example 1.

[0144] Example 16

[0145] The difference between this embodiment and embodiment 1 is that the porosity of the functional layer is adjusted to 75% by adjusting the drying temperature.

[0146] The rest of the preparation methods and parameters were the same as those in Example 1.

[0147] Comparative Example 1

[0148] The difference between this comparative example and Example 1 is that no functional layer is provided and the thickness of the structural layer is set to 12 μm.

[0149] The rest of the preparation methods and parameters were the same as those in Example 1.

[0150] Comparative Example 2

[0151] The difference between this comparative example and Example 1 is that the functional layer does not contain any functional material.

[0152] The rest of the preparation methods and parameters were the same as those in Example 1.

[0153] Comparative Example 3

[0154] This comparative example provides a negative electrode plate, which is a carbon-coated aluminum foil with a thickness of 15 μm.

[0155] Comparative Example 4

[0156] This comparative example provides a negative electrode plate, which is an aluminum foil with a thickness of 13 μm.

[0157] Performance Testing

[0158] The negative electrode sheets provided in the above embodiments and comparative examples are cold pressed and cut into a size of 58 mm×45 mm, and then assembled with the positive electrode sheets, a separator and an electrolyte to obtain a sodium ion battery. The specific steps include:

[0159] 1) Positive electrode sheet: The positive electrode active material sodium ferric pyrophosphate (NFPP), the conductive agent Super P (conductive carbon black), and the binder PVDF (polyvinylidene fluoride) are mixed in a mass ratio of 96:1:3, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry with a solid content of 50%, and stirred evenly; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector carbon-coated aluminum foil with a thickness of 15μm, so that the mass of the positive electrode active material on the positive electrode sheet is 15g / cm 2 ; Drying at 70°C to obtain a positive electrode sheet coated with a positive electrode active layer on one side; then repeating the above steps on the other side of the positive current collector to obtain a positive electrode sheet coated with a positive electrode active layer on both sides; after coating, the positive electrode sheet is cold pressed and cut into a size of 56mm×43mm for standby use, and the compaction density of the positive electrode sheet is 2g / cm 3 .

[0160] 2) Electrolyte: In a glove box, organic solvents ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) were mixed in a mass ratio of EC:EMC:DEC=30:50:20, and then sodium hexafluorophosphate (NaPF6) was added to dissolve and mix evenly to obtain an electrolyte with a sodium salt concentration of 1.15 mol / L.

[0161] 3) Diaphragm: A polyethylene film with a thickness of 15 μm (provided by Celgard Company) was used.

[0162] 4) Packaging material: 113μm aluminum-plastic composite film provided by DNP.

[0163] 5) The positive electrode sheet, separator and negative electrode sheet are correctly placed in the corresponding positions of the desktop stacking machine, so that the separator is between the positive electrode sheet and the negative electrode sheet to play a role of isolation, and wound to obtain a bare cell, each bare cell consists of 5 positive electrodes and 6 negative electrodes; the bare cell is fixed with tape to prevent the electrode sheet from shifting, the aluminum-plastic composite film is punched at a pressure of 10T to obtain an aluminum-plastic composite film with a suitable deep pit, the fixed bare cell is placed in the aluminum-plastic composite film pit for top and side sealing and ear transfer welding, and then placed in a vacuum oven at 80°C to remove moisture, and the prepared electrolyte is injected. After secondary packaging, standing, formation and degassing, a sodium ion battery is obtained.

[0164] The above-mentioned sodium ion batteries were subjected to cycle performance tests, energy density tests and rate performance tests.

[0165] The test conditions for the cycle performance include: cycling 200 times at room temperature and a charge and discharge rate of 0.2C, and calculating the capacity retention rate after 200 cycles.

[0166] The test conditions for energy density include: recording the discharge capacity at a charge and discharge rate of 0.2C at room temperature, and calculating the charge and weight energy density of a single cell.

[0167] The test conditions for rate performance include: at room temperature, recording the discharge capacity when the charge and discharge rate is 5C, dividing it by the discharge capacity at 0.2C, and calculating the 5C capacity retention rate of the battery cell.

[0168] The test results are shown in Table 1.

[0169] Table 1

[0170]

[0171] analyze:

[0172] It can be seen from the above table that the composite negative electrode plate provided by the present invention not only improves the efficiency of sodium ion deposition and stripping, thereby improving the energy density of the sodium ion battery, but also slows down the capacity decay of the sodium ion battery, significantly improving the cycle life of the sodium ion battery.

[0173] It can be seen from Example 1 and Example 5 that the functional material is a combination of MgF2 and CaO, which is more conducive to improving the kinetic properties of sodium ions and the electrochemical performance of the battery than MgF2 alone.

[0174] It can be seen from Examples 1 and 6 that the functional material is a combination of MgF2, CaO and Cu-Zn alloy, in which the metal fluoride and the metal oxide work together to have higher energy density, better rate performance and cycle stability. At the same time, the alloy material is introduced to provide a framework, which is conducive to the deposition of sodium ions, thereby increasing the energy density of the sodium ion battery, slowing down the capacity decay of the sodium ion battery, and improving the cycle life of the sodium ion battery.

[0175] It can be seen from Example 1 and Example 7 that introducing a certain content of alloy into the functional layer helps to reduce the sodium ion deposition energy and improve the kinetics of sodium ions and the rate performance of the battery cell.

[0176] It can be seen from Examples 1 and 8 that the functional layer is replaced with two functional single layers, and the mass proportion of the functional material in the functional single layer increases layer by layer in the direction away from the aluminum foil, which helps to improve the energy density of the battery cell.

[0177] It can be seen from Examples 1 and 9-10 that, within a suitable range, as the mass proportion of functional materials increases, it is beneficial to further improve the energy density of sodium ion batteries, slow down the capacity decay of sodium ion batteries, and improve the cycle life of sodium ion batteries.

[0178] It can be seen from Example 1 and Examples 11-12 that if the mass ratio of MgF2 to CaO is too small, the rate performance is poor; if the mass ratio of MgF2 to CaO is too large, the electrochemical reaction is unstable and the capacity decays rapidly.

[0179] It can be seen from Example 1 and Examples 13-14 that if the mass proportion of the functional material is too small, the energy density is low; if the mass proportion of the functional material is too large, it is not conducive to the escape of sodium ions and affects the rate performance.

[0180] It can be seen from Example 1 and Examples 15-16 that if the porosity of the functional layer is too small, it is not conducive to the battery kinetic performance and rate performance; if the porosity of the functional layer is too large, it is not conducive to the long-term cycle performance of the battery.

[0181] It can be seen from Example 1 and Comparative Example 1 that if the functional layer is not provided, the sodium ions cannot be uniformly deposited, and the cycle and rate performances are poor.

[0182] It can be seen from Example 1 and Comparative Example 2 that if the functional layer does not contain the functional material, the sodium ions cannot be uniformly deposited, and the cycle and rate performances are poor.

[0183] It can be seen from Example 1 and Comparative Example 3 that if the negative electrode plate is a carbon-coated aluminum foil with a thickness of 15 μm, the sodium ions cannot be uniformly deposited, and the cycle and rate performances are poor.

[0184] It can be seen from Example 1 and Comparative Example 4 that if the negative electrode plate is an aluminum foil with a thickness of 13 μm, the sodium ions cannot be uniformly deposited, and the cycle and rate performances are poor.

[0185] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite negative electrode sheet for a sodium ion battery, characterized in that: The composite negative electrode sheet comprises a negative electrode current collector and a negative electrode active layer arranged on at least one side surface of the negative electrode current collector; Along the direction away from the negative electrode current collector, the surface of the negative electrode active layer includes a stacked functional layer and a structural layer; The functional layer includes a first negative electrode active material, a first binder and a functional material, wherein the functional material includes a metal fluoride and / or a metal oxide; The structural layer includes a second negative electrode active material and a second binder.

2. The composite negative electrode sheet for sodium ion battery according to claim 1, characterized in that: The functional materials include metal fluorides, metal oxides and alloys; And / or, the mass ratio of the metal fluoride to the metal oxide is (0.1-100):(0.1-50); And / or, based on the mass of the functional layer, the mass of the alloy accounts for 0.1-20%; And / or, the metal fluoride comprises any one of ZnF2, MgF2, CaF2, NaF or BaF2 or a combination of at least two thereof; And / or, the metal oxide includes any one or a combination of at least two of ZnO, MgO, CuO, CaO, Al2O3, La2O3 or Ce2O3; And / or, based on the mass of the functional layer, the mass proportion of the functional material is 0.1-20%.

3. The composite negative electrode sheet for sodium ion battery according to claim 1, characterized in that: The thickness of the functional layer is 1-10 μm; And / or, the porosity of the functional layer is 20-70%.

4. The composite negative electrode sheet for sodium ion battery according to claim 1, characterized in that: The functional layer comprises at least two functional monolayers; And / or, the thickness of the functional monolayer is 0.1-5 μm; And / or, along the direction away from the negative electrode current collector, the mass proportion of the functional material in the functional single layer increases layer by layer.

5. The composite negative electrode sheet for sodium ion battery according to claim 1, characterized in that: The first binder includes any one of PVDF, PAA, PTFE, CMC or SBR or a combination of at least two thereof; And / or, based on the mass of the functional layer, the mass proportion of the first binder is 0.1-4%; And / or, the first negative electrode active material includes any one of activated carbon, expanded graphite, carbon nanotubes or hard carbon, or a combination of at least two of them.

6. The composite negative electrode sheet for sodium ion battery according to claim 1, characterized in that: The second negative electrode active material comprises any one of activated carbon, expanded graphite, carbon nanotubes or hard carbon, or a combination of at least two thereof; And / or, based on the mass of the structural layer, the mass proportion of the second negative electrode active material is 80-98%; And / or, the second binder includes any one of PVDF, PAA, PTFE, CMC or SBR, or a combination of at least two thereof.

7. The composite negative electrode sheet for sodium ion battery according to claim 1, characterized in that: The thickness of the structural layer is 10-60 μm; And / or, the porosity of the structural layer is 30-85%.

8. A method for preparing a composite negative electrode sheet for a sodium ion battery according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The first negative electrode active material, the first binder, the functional material and the solvent are mixed to obtain a functional layer slurry; the second negative electrode active material, the second binder and the solvent are mixed to obtain a structural layer slurry; wherein the functional material includes metal fluoride and / or metal oxide; The functional layer slurry is coated on at least one side surface of the negative electrode current collector to form a functional layer, and then the structural layer slurry is coated on the outer surface of the functional layer to form a structural layer to obtain the composite negative electrode sheet for the sodium ion battery.

9. The preparation method according to claim 8, characterized in that: The preparation method comprises the following steps: (1) mixing a first negative electrode active material, a first binder and a functional material, and then adding a solvent to prepare a functional layer slurry with a solid content of 30-50%; wherein the functional material includes metal fluoride, metal oxide and alloy; The second negative electrode active material and the second binder are mixed, and then a solvent is added to prepare a structural layer slurry with a solid content of 30-50%; (2) coating the functional layer slurry on one side of the negative electrode current collector and obtaining the functional layer after drying; The structural layer slurry is coated on the outer surface of the functional layer, and dried to obtain the structural layer; (3) Repeat step (2) on the other side of the negative electrode current collector to obtain a composite negative electrode sheet for a sodium ion battery coated with a negative electrode active layer on both sides.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the composite negative electrode sheet for a sodium ion battery according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Sodium metal negative electrode protective layer, sodium metal negative electrode and preparation method and application thereof

    CN112531145A

  • Negative pole piece, lithium ion battery monomer, lithium ion battery and electric equipment

    CN115832213A

  • Sodium-ion battery composite negative electrode, battery and preparation method of negative electrode

    CN116825962A

  • Negative pole piece, preparation method thereof and sodium ion battery

    CN118522847A

  • Electrochemical cell

    US20100178546A1

Cited By

  • Negative pole piece, sodium battery and energy storage device

    CN121687854A